KUALITAS SUSU KAMBING PERANAKAN ETAWA PADA BERBAGAI PERIODE LAKTASI DITINJAU DARI SIFAT FISIK (Studi Kasus di Peternakan Kambing Perah Telaga Rizky, Yosodadi, Kota Metro) - Muhammad Ibnu Sholeh; Sulastri Sulastri; Arif Qisthon; Ali Husni (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the physical quality of Ettawa Grade (PE) goat milk at various lactation periods in East Metro District, Metro City, Lampung Province, and to determine whether the quality of PE goat milk was in accordance with the standards set out in SNI No 01-3141-1998. This research was conducted on September 16, 2019, at the farm owned by Mr. Setiono Heri Winarko on Jalan Sepat, Yosodadi, East Metro District, Metro City, Lampung Province. Physical quality testing of PE goat milk was carried out at the Animal Production and Reproduction Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The research was conducted using a case study method. Data collected was using primary and secondary data. The variables observed included the organoleptic tests, which were color, aroma, taste, and acceptability test of PE goat's milk; and physical tests including specific gravity, boiling test, alcohol test for the acidity (pH) of PE goat milk. The results of the research on the lactation color test 1, 2, 3, and 4 were 3.53, 3.53, 3.22, 3.12, respectively. Aroma test results were 3.56, 3.70, 3.54, and 3.40 for lactation 1, 2, 3, and 4, respectively. The taste tests for lactation 1, 2, 3, and 4 were 3.50, 3.78, 3.54, and 3.45, respectively. The acceptance test result were 3.50, 3.86, 3.72, and 3.63 for lactation 1, 2, 3, and 4, respectively. Density test of milk for lactation 1, 2, 3, and 4 were 1.028; 1.030; 1.036; 1.033. In the boiling test and lactation alcohol 1-4, there was no clod (-), and the pH test was 6.39, 6.62, 6.60, and 6.57 in lactation 1, 2, 3, and 4, respectively. It can be concluded that the results of the above studies have met the standards set out in SNI No 01-3141-1998. Keywords: Etawa crossbreed goat, Lactation period, Physical characteristics